Customer involvement in new product development of tile and ceramic industry. (2018) - Mirfakhradini, Seyed Heydar; Safari, Khalil; Shaabani, Akram; Valaei, Naser; Mohammadi, Khadijeh
In order to have new product development and attract customers' involvement, a holistic approach is required within which consumers, manufacturers, sellers, designers and other stakeholders are gathered together effectively. Understanding the related factors that influence involvement of each stakeholder is crucial for achieving a sustainable competitive advantage. Therefore, this study is aimed to examine the effect and importance of customer involvement in new product development. The theoretical model is proposed based on a rigorous literature review and hypotheses are developed. In this survey - solidarity and cross sectional sampling is selected for considering the judgment of 150 managers, suppliers; and sellers (wholesalers and retailers) in Yazd tile and ceramic industry. The data is collected through questionnaires and the partial least squares-structural equation modelling (PLS-SEM) approach is applied. Research results indicated that two variables of marketing strategy and contextual factors explain changes in customer involvement as much as 24%, 34%, and the relationship between customer involvement and new product development is positively significant. The relationship between customer involvement and new product performance is also supported.